Infinite Series

Algebra Level 2

Evaluate ( 6 + ( 6 + ( 6 + ( . . . ) 1 2 ) 1 2 ) 1 2 ) 1 2 (6+(6+(6+(...)^{\frac{1}{2}})^{\frac{1}{2}})^{\frac{1}{2}})^{\frac{1}{2}}


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Justin Wong
Apr 13, 2014

Write the expression in a more recognizable form and set it equal to a value x x so that x = 6 + 6 + 6 + . . . x=\sqrt{6+\sqrt{6+\sqrt{6+...}}} . The expression repeats at the second square root, so we can substitute x x in that spot. x = 6 + x x=\sqrt{6+x} , then square and rearrange to get the quadratic x 2 x 6 = 0 x^2-x-6=0 . Solving yields two solutions, 3 3 and 2 -2 , but you take the positive solution 3 \boxed{3} .

I thought it is 6^1/2........

Anuj Shikarkhane - 6 years, 11 months ago

The expression can be written in a more familiar form; ( 6 + ( 6 + ( 6 + ( 6 + ( ) 1 2 ) 1 2 ) 1 2 ) 1 2 ) 1 2 = 6 + 6 + 6 + \color{#3D99F6}{(6+(6+(6+(6+(\dotsm)^{\frac{1}{2}})^{\frac{1}{2}})^{\frac{1}{2}})^{\frac{1}{2}})^{\frac{1}{2}}=\sqrt{6+\sqrt{6+\sqrt{6+\sqrt{\dotsm}}}}} Now let the above expression be equal to x x .Then the expression can be written as; x = 6 + x x 2 = 6 + x x 2 x 6 = 0 ( x 3 ) ( x + 2 ) = 0 x = 3 o r x = 2 \color{#20A900}{x=\sqrt{6+x}\\x^2=6+x\\x^2-x-6=0\\ (x-3)(x+2)=0\\x=3\;or\;x=-2} As the expression is positive so the answer is 3 \boxed{3}

Saurabh Mallik
Jun 14, 2014

Let:

x = 6 + 6 + 6 + 6..... x=\sqrt{6+\sqrt{6+\sqrt{6+\sqrt{6.....}}}}

x = 6 + x x=\sqrt{6+x}

Squaring both sides:

x 2 = 6 + x x^{2}=6+x

x 2 x 6 = 0 x^{2}-x-6=0

x 2 3 x + 2 x 6 = 0 x^{2}-3x+2x-6=0

x ( x 3 ) + 2 ( x 3 ) = 0 x(x-3)+2(x-3)=0

( x 3 ) ( x + 2 ) = 0 (x-3)(x+2)=0

So, the values of x = 3 =3 and 2 -2

But, x x cannot be negative, since square root of negative integers is not possible.

Thus, the answer is: x = 3 x=\boxed{3}

But the square root of negative numbers can be m written in the terms of iota therefore square root of -2 can be written as 0.414i(i=iota). Therefore answers can be both 3 and -2.

Sourabh shukla - 6 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...